Child Perspectives and Children’s Perspectives – a Concern for Teachers in Preschool - Thulin, Susanne; Jonsson, Agneta (Educare, 2014)
The aim of this article is to study and problematize the importance of the communicative approach of teachers related to child perspectives and children’s perspectives as well as the meaning for children's learning. The article is based on empirical material from two observational studies of preschool teachers at two Swedish preschools, children aged between 1 and 6. One theoretical basis of this article is that teachers not only ought to observe the understanding children are carriers of. Teachers also have to make use of the understanding in the continuing learning process to be able to support children's learning. Children need to be given the opportunity to be aware of and experience how their own understanding can be linked to new experiences. The results reveal qualitatively distinct communicative approaches with regard to how teachers verbally engage in and make use of what children are occupied with. The discussion relates this to child perspectives combined with children’s perspectives as a didactic basis.